CULTURAL CONSERVATION MANAGEMENT BASED ON LOCAL WISDOM THROUGH AN UNDERSTANDING OF THE INFLUENCE OF CULTURAL ACCULTURE IN THE PAST ON PALEMBANG SONGKET MOTIFS - Desloehal Djumrianti; Lisnini Lisnini; Andika Fathan Abdillah (Jurnal Manajemen, 2024)
This research is about Palembang local wisdom, focusing on Songket fabric. This research looks at the influence of acculturation of Arabic, Chinese, and Bangka cultures in the past on Palembang Songket motifs, especially seen from social, artistic and cultural factors. Thus, the purpose of the research is to examine how the management of the conservation of Palembang's local wisdom culture through understanding how the influence of acculturation in the past has created several Songket motifs that exist today. The method of data collection in this research is by using questionnaires to 100 selected respondents and semi-structured interviews to several key informants. By using SPSS version 25 to process and analyse the data, it was found that the interaction between people from foreign countries in the past and Palembang people has contributed to the existence of Songket motifs that exist today. Mainly due to social factors, art, and customs, about 50.4% influenced overall. In addition, the study shows that the conservation management of Palembang Songket culture is carried out by applying the conservation function.